Study on stage method of reservoir flood season - Yu Song (Elsevier, 2022)
Due to the influence of the monsoon, river runoff in most of China’s river basins is mainly concentrated in the flood season. The distribution is extremely uneven during the year and between the year. It needs to be fully utilized by the reservoir to bring serious challenges to the daily management. Therefore, analyzing the seasonal variation of storm floods, scientifically and rationally staging the flood season can not only give full play to the comprehensive benefits of the reservoir, but also be an inevitable requirement for coordinating reservoir flood control and power generation. Aiming at the several commonly used methods of flood season staging, the case study is carried out, and the applicable conditions are analyzed. Based on these, three new staging methods are proposed. Among them, the improved change point analysis method adopts the linear and nonlinear joint fitting, which improves the commonly used mean value calculation method. In theory, the non-uniformity and seasonality of the reservoir water are more carefully considered, and the flood season is considered to some extent. The distribution law and continuity of floods along the time course; the projection method has a similar theoretical system with the vector statistical method based on the annual maximum sampling method, both of which are based on the intensity of the points, the difference is the point of the latter is projected on the circumference, the partitioning result is selected by manual experience, and the human influence factor is large. The new method is to project the point on the straight line, and quantitatively gives the partitioning method, and is also applicable to the maximum flow of different sequences. The case of the same time, the dynamic clustering method divides the sample set into several subsets according to the similarity between samples, and has the advantage that the calculation amount is small and the genus of the sample can be changed compared with the system clustering method. The research results can provide reference for the reasonable adjustment of the reservoir flood season.